Etika Teknologi Informasi dalam Dunia Pendidikan: Tinjauan Literatur atas Penggunaan AI dan Isu Plagiarisme Akademik - Khalida, Rahma; Rahmandri, Ananda; Matilda Magren, Sahira Ayla; Nurmiati, Evy (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2025)
The advancement of artificial intelligence (AI) has had a significant impact on higher education, particularly regarding plagiarism ethics. This study employs a Systematic Literature Review (SLR) of nine articles published between 2021 and 2025 to analyze the influence of ChatGPT on student behavior, academic integrity, and institutional policies. Findings reveal that students are more permissive toward AI-based plagiarism compared to copying from human work. A cross-cultural survey reported that 61% of students in collectivist countries considered ChatGPT acceptable as a learning assistant, compared to only 37% in individualistic countries. From the detection perspective, integrating Natural Language Processing (NLP) improved system accuracy from 72% (conventional) to 89% (AI-based). Another study reported AI effectiveness with 85% recall and 81% precision, higher than the traditional system’s 65% recall. Additionally, 74% of higher education institutions in developing countries were found to lack explicit guidelines on AI use. These findings highlight that AI challenges are not only technical but also ethical, requiring digital literacy programs and comprehensive policies to safeguard academic integrity.